Model And Analysis Of Wind Speed Profile Using Artificial Neural Network - Feasibility Study In Peninsular Malaysia - Kamarudin, Muhammad Nizam; Husain, Abdul Rashid; Ahmad, Mohamad Noh; Mohamed, Zaharuddin (Penerbit UTM Press, 2015)
-